Simplify 11(2x + 3).

Question

Asked 9/24/2012 11:03:48 AM

Updated 6/21/2014 1:28:55 PM

9 Answers/Comments

Flagged by andrewpallarca [6/21/2014 1:27:23 PM], Unflagged by andrewpallarca [6/21/2014 1:28:14 PM]

g
googletag.cmd.push(function() { googletag.display('div-gpt-ad-1564665647093-0'); });

OxTornado007|Points 5488|

stan_r|Points 1332|

debnjerry|Points 37494|

(243) (x^10) (z^5) = 243 x^10 z5 ;

So the answer is 243 x^10 z5

latefisher|Points 2948|

latefisher|Points 2948|

OxTornado007|Points 5488|

migzptz|Points 6669|

trantien2000|Points 170|

eitak1987|Points 55|

goodenough|Points 145|

Expert answered|arraarceo|Points 90|

Question

Asked 9/24/2012 11:03:48 AM

Updated 6/21/2014 1:28:55 PM

9 Answers/Comments

Flagged by andrewpallarca [6/21/2014 1:27:23 PM], Unflagged by andrewpallarca [6/21/2014 1:28:14 PM]

Rating

8

5m2 - mn + 4n + 7 has FOUR terms.

Added 6/21/2014 1:25:18 PM

This answer has been confirmed as correct and helpful.

8

11(2x + 3) = 22x + 33

Added 6/21/2014 1:25:30 PM

This answer has been confirmed as correct and helpful.

8

8(3 - 2x) = -16x + 24

Added 6/21/2014 1:25:46 PM

This answer has been confirmed as correct and helpful.

8

3x + 3 + 2 = 3x + 5

Added 6/21/2014 1:26:01 PM

This answer has been confirmed as correct and helpful.

8

3x + (-12x) - 5x

= 3x - 12x - 5x

= -9x - 5x

= -14x

= 3x - 12x - 5x

= -9x - 5x

= -14x

Added 6/21/2014 1:26:43 PM

This answer has been confirmed as correct and helpful.

8

5x + 4x + 1 = 9x + 1

Added 6/21/2014 1:27:05 PM

This answer has been confirmed as correct and helpful.

8

6(x + 2) + 7 = 6x + 12 + 7 = 6x + 19

Added 6/21/2014 1:27:40 PM

This answer has been confirmed as correct and helpful.

8

-4(N + 9) = -4N - 36

Added 6/21/2014 1:28:07 PM

This answer has been confirmed as correct and helpful.

8

(5b)(-3a) = -15ab

Added 6/21/2014 1:28:55 PM

This answer has been confirmed as correct and helpful.

Can a blood clot in the brain cause a stroke? User: Macular degeneration can cause tooth loss.

Question

Updated 5/14/2014 12:07:15 AM

2 Answers/Comments

Simplify -2[9 - (x + 7)]. **Weegy:** 2(4z-5)/-7+5z This is the simplified form. **User:** Which of the following expressions is equal to 5 - 2m?
7 - 2(m + 1)
7 - (2m - 5)
7 - 2(m - 2) **User:** Simplify 6(x + y) + (x - y). **Weegy:** I'm sorry, do you have a question I can help you with today? **User:** How do you Simplify 6(x + y) + (x - y). **Weegy:** I'm sorry, do you have a question I can help you with today? (More)

Question

Updated 6/21/2014 1:21:35 PM

2 Answers/Comments

-2[9 - (x + 7)]

= -2[-x + 2]

= 2x - 4

= -2[-x + 2]

= 2x - 4

Added 6/21/2014 1:20:53 PM

This answer has been confirmed as correct and helpful.

6(x + y) + (x - y)

= (6x + 6y) + (x - y)

= 7x + 5y

= (6x + 6y) + (x - y)

= 7x + 5y

Added 6/21/2014 1:21:35 PM

This answer has been confirmed as correct and helpful.

34,850,588

questions answered

There are no comments.